2012
DOI: 10.1585/pfr.7.2403063
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Current Ramp-Up Phase for Hybrid ITER Scenario

Abstract: This paper reports on a systematic effort to optimize the current ramp-up phase for the ITER hybrid scenario, and to assess the sensitivity of the results to the assumptions made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Starting with the current ramp-up phase an impact of external heating and current drive waveforms, timing of the L-H transition and plasma current waveform on the target q-profile and resistive flux consumption at the end of the current ramp-up have been investigated [43,44]. It has been shown that the q-profile with q 0 > 1 can be reached at the end of the current ramp-up phase with the heating systems available at ITER.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting with the current ramp-up phase an impact of external heating and current drive waveforms, timing of the L-H transition and plasma current waveform on the target q-profile and resistive flux consumption at the end of the current ramp-up have been investigated [43,44]. It has been shown that the q-profile with q 0 > 1 can be reached at the end of the current ramp-up phase with the heating systems available at ITER.…”
Section: Discussionmentioning
confidence: 99%
“…Access condition to the class of hybrid-like q-profiles (i.e. flat in the core and slightly above unity with a high magnetic shear in the gradient zone) during the prelude phase of the scenario is investigated with particular attention in this section [42][43][44]. The plasma current ramp-up phase is a critical phase of the scenario preparation where the optimized q-profile should be reached while deleterious MHD instabilities for confinement and stability have to be avoided, flux consumption has to be minimized, and this has to be achieved within ITER operational constrain.…”
Section: Current Profile Optimization During Current Ramp-up Phasementioning
confidence: 99%
“…Validation on the ramp-up phase of JET, AUG and Tore Supra [6,8,9] has shown that both empirical scaling based models and the semi-empirical Bohm/gyro-Bohm model (L-mode version, internal transport barrier (ITB) shear function off, [10]) yield a good reproduction of this phase for considered discharges, in terms of the T e profile and l i . Therefore these two models have been used in the reported work.…”
Section: Introductionmentioning
confidence: 99%
“…The current ramp-up phase in tokamaks has recently attracted the attention of experimentalists [1][2][3] and modellers [1,[4][5][6] in connection with future experiments on ITER. The important objectives of the current ramp-up phase on ITER are maintenance of a current density profile compatible with vertical stability of the plasma column [7] and the formation of the target q-profile favourable for subsequent burn phase (with q 0 above one for an extended sawtoothfree H-mode and hybrid scenario or reversed q-profile for the advanced operation with an internal transport barrier (ITB)) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Later on the validation of the Bohm-gyroBohm model [10] has been performed also for OH and LHCD assisted current ramp-up phase of the H-mode discharges of JET [6]. Finally, the empirical formula for the thermal electron diffusivity which has a parabolic profile multiplied by a free coefficient adjusted at each time step to provide a prescribed H 98y factor has been validated against the OH current ramp-up discharges of JET, performed at two different current ramp rates, and applied to the modelling of the ITER ramp-up phase [5].…”
Section: Introductionmentioning
confidence: 99%